If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(2n + -6) = 7(n + 3) Reorder the terms: -7(-6 + 2n) = 7(n + 3) (-6 * -7 + 2n * -7) = 7(n + 3) (42 + -14n) = 7(n + 3) Reorder the terms: 42 + -14n = 7(3 + n) 42 + -14n = (3 * 7 + n * 7) 42 + -14n = (21 + 7n) Solving 42 + -14n = 21 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. 42 + -14n + -7n = 21 + 7n + -7n Combine like terms: -14n + -7n = -21n 42 + -21n = 21 + 7n + -7n Combine like terms: 7n + -7n = 0 42 + -21n = 21 + 0 42 + -21n = 21 Add '-42' to each side of the equation. 42 + -42 + -21n = 21 + -42 Combine like terms: 42 + -42 = 0 0 + -21n = 21 + -42 -21n = 21 + -42 Combine like terms: 21 + -42 = -21 -21n = -21 Divide each side by '-21'. n = 1 Simplifying n = 1
| 8=z-7 | | 3+9z-8h= | | 7x-8=3(x+2) | | 15x-9x=48 | | 8b-a=-3 | | 4(3d-2)=32 | | x^2+2x-52=0 | | -6(5+3x)=14 | | cos(6x)=cos(4x) | | 14.2=0.4(20m-7.8) | | 24+9=21 | | 24+9= | | a+4b=6 | | 12(2e+3)=96 | | -4z-5=8z+3 | | C=20n+8 | | (2z+9)(7-z)=0 | | f(x)=-8x^2+8x+9 | | y=x^2ln(3x) | | n+33=25 | | y=3*(-3)+10 | | -7r=7(8+3r) | | 5ksquared=180 | | x^2+4x-20y+50=0 | | 7t-8=7+t | | m-48=-18 | | -x+7=-26+2x | | 3.92*1000000000000= | | (x-2)[2x-2(3+x)]-12= | | x^3+8x^2+19x+12=0 | | x+5*(3x+10)=2 | | s^3+8s^2+19s+12=0 |